CLOGMIA ALBIPUNCTATA: A SYSTEMATIC REVIEW OF FREQUENCY STUDIES - Muna Ibrahim jassem; Athraa Adnan Mahdi (Scholar Express Journals, 2022)
Clogmia albipunctata (Diptera: Psychodidae), It is one of the widespread and universal species that abounds in tropical and temperate climates around the world. It is conspicuous and abundant and is widely found in human environments like kitchens, sewage water and bathrooms, and it multiplies in water-filled tree pits
Keywords: Clogmia albipunctata; Psychodidae; Reverse-engineering and Moth midge; found